Socioeconomic Inequalities and Academic Performance: Analysis of Saeb/Brazil and Simce/Chile Results in 2019 - Rios-Munoz, D (UNIV ESTADUAL PAULISTA JULIO MESQUITA FILHO, FAC CIENCIAS & TECNOLOGIA, 2024)
: This paper was developed with the aim of analyzing the influence of socioeconomic factors on students academic performance in standardized assessments administered by the Sistema de Avalia & ccedil;& atilde;o da Educa & ccedil;& atilde;o B & aacute;sica in Brazil and the pelo Sistema de Medici & oacute;n de la Calidad de la Educaci & oacute;n in Chile. This is a comparative mixed methods research with a sequential exploratory perspective, predominantly quantitative, which uses official data obtained through queries to the electronic portals of both countries. The results confirm the association between students socioeconomic status and their academic success, with a stronger emphasis on the intensity of this relationship in the most extreme socioeconomic categories. This highlights the pressing need to develop innovative strategies to balance academic performance expectations among students from different social backgrounds. This challenge becomes even more significant in light of the ongoing educational changes in both countries, particularly the reforms in their academic assessment systems.